Female Athletes' Experiences Applying Basic Pencak Silat Skills in the Professional World - Ishak, Mega Maulidia; Al Uyun, Dhia; Wahyuni, Lilik (Borong Newinera Publisher, 2024)
Pencak silat is classified as a type of hard sport and if a woman decides to learn pencak silat it is considered taboo or inappropriate. However, the phenomenon found by researchers in the field is that there are female athletes who dare to break away from society's construction of women who are involved in pencak silat accompanied by the contribution of female athletes in achievements in sporting events, especially in the martial arts sport of pencak silat. This shows that women tend not to be weak. Based on the initial explanation that has been put forward, the author is interested in exploring this research which focuses on the experiences of female athletes. This research was carried out in the form of experience in using basic pencak silat skills. This research is a descriptive qualitative literature and participatory research. Based on research results, gender equality is still a hot issue to be discussed throughout the world, various efforts have been made to improve gender equality in various fields, including sports. In the world of sports, men and women should have the same rights to participate, excel and pursue sports professionally, but there are still many people who consider that sport is a masculine activity, where it is identified with men's and women's activities, which they feel is lacking. suitable for being involved in the world of sports.